Financial performance of sharia and non-sharia life insurance: A comparative analysis - Firdausi Mustofa, Ardyan; Sri Janatin, Anisa (JIFA (Journal of Islamic Finance and Accounting), 2022)
The emergence of Islamic insurance as a financial solution for Muslim communities, especially in Muslim-majority countries, is an intriguing topic. This study aims to evaluate the financial performance of Sharia-compliant life insurance in Indonesia and its market presence. Specifically, it compares the financial performance of non-Sharia and Sharia life insurance companies using the Early Warning System (EWS) and Risk-Based Capital (RBC). The EWS evaluation measures capital adequacy ratio, claim expense ratio, liquidity ratio, and own retention ratio, while RBC measures solvency ratio. The results of hypothesis testing, using the Mann-Whitney U test, reveal a significant difference between the financial performance of non-Sharia and Sharia life insurance companies based on EWS. However, there is no significant difference between their financial performance based on RBC's solvency ratio. The findings of this study imply that, as a whole, sharia-compliant insurance outperforms its non-sharia counterparts. Despite the relatively small sample size, these results offer a ray of hope for Islamic financial institutions to pursue further growth and development.